Young adult preference analysis on the attributes of COVID-19 vaccine in the Philippines: A conjoint analysis approach - Ardvin Kester S. Ong; Yogi Tri Prasetyo; Fae Coleen Lagura; Rochelle Nicole Ramos; Jose Ma Luis Salazar; Keenan Mark Sigua; Jomy Anne Villas; Thanatorn Chuenyindee; Reny Nadlifatin; Satria Fadil Persada; Kriengkrai Thana (Elsevier, 2022)
Objective: Vaccines are utilized to prevent the severity of illnesses like the COVID-19 virus. Currently, there are a lot of COVID-19 vaccines available in the market like Pfizer, Moderna, AstraZeneca, Johnson and Johnson, and Sinovac. This research aimed to analyze the preference on the existing vaccine attributes of COVID-19. Study design: Specifically, this study considered 7 attributes such as cost, brand, recommendations, efficacy, side effects, vaccine type, and dose. Methods: A conjoint analysis with orthogonal design was utilized and 865 respondents were participated. Results: The result showed that consumers considered brand as the highest attribute, specifically Pfizer and Moderna among other brands. Moreover, the efficacy of 90% and higher were the preferred vaccine with 1 in 100 patient side effects reported. It was seen that safety and effectiveness is the priority in choosing a COVID-19 vaccine. Interestingly, the knowledge and understanding of the COVID-19 vaccine was found to drive consumer's preference for the vaccines available. Conclusions: The findings of this study could be utilized by the government to increase the willingness to be vaccinated. Lastly, the result of this study would pave a way to promote herd immunity to help fight the COVID-19 pandemic worldwide.